PENGARUH PAD TERHADAP KINERJA MANAJERIAL PEMERINTAH DAERAH KABUPATEN ACEH UTARA - Sa’diyah, Halimatus; Putri, Yetty Tri (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2015)
The aim of this research is to determine the influence of District Own SourceRevenue to government managerial performance of Aceh Utara District. The sampleselection using target sampling, that involves 75 respondents in Aceh Utara districtgovernment. Primary data were obtained through questionnaires. Data wascollected through questionnaires survey method is to provide answers to theproblems faced by explaining the relationships between variables with hypothesistesting.The research result shows that 78,3% of District Own Resource Revenuehas contribution to government managerial performance in Aceh Utara District.Meanwhile 21,7% was another influenced factors that was not observed in thisresearch. The result of this study also indicates the hypothesis that the district ownrevenue positively influences participation on government managerial performancecan be proved.Keyword: District own resource revenue, government managerial performance.